Semiotic Touch in Interpreting Poetry - Iskandarsyah Siregar (Britain International for Academic Research (BIAR) Publisher, 2022)
Poetry is a poetic work of art. The poetic word already contains a unique beauty for poetry. Poetry is a medium for people who want to express their feelings. The language used by poetry is trimmer and more intensive than the language used for daily conversation. This intensive disclosure is what makes poetry valuable in the eyes of humans. Semiotics is a scientific discipline and analytical method that can examine the signs contained in an object to find out the meaning contained in the object. This study uses a literature review method where the technique used is to collect reading materials and literature specifically and then analyze the content of the study based on the focus of the problems discussed. After finding the matrix or keywords in a poem, the next step in studying poetry based on the approach is determining the theme. The theme is determined to get the main essence in a poem.